The Influence of Work Ethic and Organizational Commitment on Employee Performance and the Role of Work Discipline as a Mediating Variable - Rahmawati, Widiya; Survival, Survival; Mas, Nasharuddin (International Journal of Accounting and Management Research, 2026)
This study examines the effects of work ethic and organizational commitment on employee performance, with work discipline serving as a mediating variable among employees at Senyum World Hotel in Batu City. A quantitative explanatory survey approach was applied, using a five-point Likert-scale questionnaire distributed to employees with at least 1 year of work experience. Data analysis was conducted using PLS-SEM with SmartPLS version 4.0.  The results indicate that work ethic and work discipline have a significant positive effect on employee performance. Organizational commitment does not directly influence performance but significantly affects work discipline. Furthermore, work discipline does not mediate the relationship between work ethic and employee performance, yet it fully mediates the relationship between organizational commitment and employee performance. These findings suggest that organizational commitment contributes to performance only when it is translated into disciplined work behavior. This study is limited to a single hotel, which may restrict the generalizability of the findings, but it provides practical implications for hotel management to prioritize strengthening work discipline to enhance employee performance.